The perfumist of Paris - Joshi, Alka (Joshi, Alka. Jaipur trilogy, 2023)
After being tasked with her first major project for the master perfumer, Radha travels to India, enlisting the help of her sisters and the courtesans of Agra, but discovers that the son she gave up years earlier is heading to locate her in Paris--threatening her marriage and carefully managed world.